PENEGAKAN HUKUM TERHADAP PROSES HUKUM PEMBUKTIAN TERBALIK TERBATAS DALAM PERKARA PIDANA KORUPSI - Zulkifli, Mizar Gustian (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTÂ Regarding the effectiveness of inverse evidence cannot be explained with certainty. This is because in general the juridical rule that this applies to everyone who is ensnared or becomes a defendant is given the opportunity to prove. According to research, usually in terms of proof, the defendant can say that his wealth is obtained from inheritance or grants. So in this case the relationship between the prosecutor and the defendant in the verification. In investigating corruption cases the obstacles faced are usually at the time of verification, because in this case it is very risky and complicated and to say certainty in this case it is necessary to have an expert witness who is expected to help. So even though there is a corruption case, it cannot necessarily be that the investigator immediately says that there is a state loss, but the investigator must carefully handle and overcome it. In the case of reversing proof the obstacles that exist include investigators to find the criminal offense of the defendant and to file offenses find difficulties if if it turns out in the process is not true. Reverse proof is the right of the suspect to defend himself for the accusation based on the evidence. Administratively, the obstacles that exist are among others in the handling of notification letters to the local government, where in this case the regional level must be known by the governor, and for the central level must be known by the president. Besides the above, it is burdensome to get preliminary evidence in conducting an investigation.Â Keywords : evidentiary law, corruption